Students’ Perception of Cultural Literacy Development in Higher Education - Awaludin Rizal; Syarifuddin Dollah; Amirullah Abduh; Baso Jabu; Muhammad Basri; Yunitari Mustikawati; Abdurrahman Hi. Usman (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This study investigated the EFL students' perceptions of cultural literacy development in higher education. Method: The research design was an ethnographic study. The study was conducted in two private and state universities in Indonesia. The subjects were students from the English education department at two universities. The researcher chose four students from each university as research subjects who know and understand more about cultural literacy development. The technique for analyzing data in the ethnographic study was descriptive labels, selecting, identifying, generalizing, and noting. Result: This study's findings showed that in higher education, two students have a high perception, one has a moderate, and the last one has a low perception of cultural literacy development in the academic context. Each student’s category generally has a different impact on the development of their cultural literacy in the academic context. Novelty: This study produces the Makugawene (harmonic) Cultural Literacy model to develop EFL students' cultural literacy in higher education.